Una nota sobre las consecuencias eticas del maltusianismo actual - Viguiristi, Fernando De La Iglesia (Gregorianum, 2020)
Malthus’s apocalyptic prophecy was not fulfilled. In fact, the Malthusian demonwas defeated by both the Industrial Revolution and the Green Revolution. However,the limited nature of our available resources and environmental sustainability, nowcalled into question by climate change, revive this problem of notable ethical consequences.